Papain-stabilized silver nanoclusters: dual emission and ratiometric fluorescent sensing of ferrous ions. Issue 7 (22nd January 2019) - Mo, Qinchao; Jia, Minna; Zhuang, Peifeng; Yang, Simin; Su, Wanting; Zhu, Yixuan; Shao, Na; Zhao, Meiping
Abstract : Herein, a dual emissive fluorescent probe for Fe 2+ based on papain-stabilized Ag nanoclusters was developed. Abstract : Herein, a dual emissive fluorescent probe based on papain-stabilized Ag nanoclusters was developed. The as-prepared papain–Ag NCs showed a ratiometric fluorescent response to Fe 2+, while other cations and anions had no effects on the fluorescence of the papain–Ag NCs. The emissions at 454 nm and 647 nm both decreased and the ratio of the fluorescence intensity at the two wavelengths ( F 454 / F 647 ) had a good linear relationship with the concentration of Fe 2+ . This probe could be used for detecting Fe 2+ in the range from 1.5 to 120.0 μmol L −1 with a detection limit of 500 nmol L −1, which was comparable to or better than those of some other fluorescence approaches for Fe 2+ sensing. The responding mechanism was attributed to the chelation of glycine (Gly) residue in the papain ligand with Fe 2+, which led to the fluorescence quenching of the papain ligand at 454 nm due to the static quenching effect and reduced the charge transfer from the papain ligand to Ag NCs resulting in the fluorescence quenching of Ag NCs at 647 nm. Moreover, the papain–Ag NC probe was extended to the detection of Fe 2+ in a real sample of ferrous lactate oral solution with satisfactory results compared with the standard 1, 10-phenanthroline method.